The theoretical basis of the concept of extremism (Journal of actual problems of jurisprudence, 2018)
Taking into account the international nature of the crime is a menace to society of extremism , and says many nationalities and faiths to maintain unity for the country to become its a major topic of the day. Focused on the definition of a dangerous phenomenon for the legislation in the fight against extremism. Help pointed out mistakes. Scientific analysis of the theoretical definition of extremism. Kazakhstan and foreign researchers as a result of a variety of thoughts and conclusions of the analysis carried out by the definition of the term extremism, he made a recommendation.Key words: extremism, terrorism, radicalism, fundamentalism, ideological phenomenon.